Modal-epistemic variants of Shapiro’s system of Epistemic Arithmetic - Horsten, Leon (My University, 1994)
This paper presents formalizations of classical first-order arithmetic which contain a modal and an epistemic operator. The embedding under variants of GodeΓs translation of Intuitionistic arithmetic in such systems is discussed, and for one modal-epistemic system of arithmetic a possible worlds semantics is given.
Keywords: 100